CHARTING SOUTH AFRICA’S GLOBAL MARITIME FOREIGN POLICY AND ITS GLOBAL AND REGIONAL MEMBERSHIPS IN THE MARITIME REALM - Surbun, Vishal (Scientia Militaria - South African Journal of Military Studies, 2020)
South Africa’s re-entry into the international arena has led to the ratification of several global and regional maritime instruments. In addition, South Africa has been admitted to various international institutions and fora in the maritime space. A key consideration in this regard is whether there is an underlying global maritime foreign policy that underscores South Africa’s contributions, interactions and responsibilities in these fora. South Africa does not have a global maritime foreign policy which is contained in an explicit policy document. This article therefore charts how various domestic and continental policy documents and ministerial statements thread together a foundational base for a global maritime foreign policy. What emerges is the primacy of African interests as the golden thread of this foundational base. The article then considers South Africa’s practical engagement through a description and categorisation of its membership of global and regional organisations in the maritime realm. The article finally narrows the focus to one organisation, the Indian Ocean Rim Association (IORA) as a platform to consolidate the foundations for a global maritime foreign policy for South Africa. The article concludes by pointing out nuanced factors that should be acknowledged for South Africa to exercise strategic power and influence over policy in the global and regional maritime realm.